Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

What is the answer x + 2x + 3(x + 4) = 5x - 6

A. 13

B. -3/5

C. -10

D. -18


Sagot :

Answer:

x= -18

Step-by-step explanation:

x + 2x + 3(x + 4) = 5x-6

Distribute

x+2x+3x+12 = 5x-6

Combine like terms

6x +12 = 5x-6

Subtract 5x from each side

6x+12 -5x= 5x-6-5x

x+12 = -6

Subtract 12 from each side

x+12-12 = -6-12

x= -18

Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.